2021
DOI: 10.3390/antiox10040612
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants of Natural Products

Abstract: Antioxidant ingredients are known to contribute to the beneficial effects of natural products in health promotion as well as disease prevention by reducing oxidative stress, caused by reactive oxygen or nitrogen species, in biological systems [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[27] In this study, the milk yield in SIF-treated mice showed an increasing trend in a foodintake-independent manner, which suggests the effect is associated to the improved antioxidant capacity and augmented utilization of nutrients induced by SIF. [28] Increased heat production in mammary gland development and lactogenesis triggers heat stress and is accompanied by the production of a large number of free radicals in order to maintain energy equilibrium. [29] A previously published study showed that SIF increased antioxidant capacity among postmenopausal females.…”
Section: Discussionmentioning
confidence: 99%
“…[27] In this study, the milk yield in SIF-treated mice showed an increasing trend in a foodintake-independent manner, which suggests the effect is associated to the improved antioxidant capacity and augmented utilization of nutrients induced by SIF. [28] Increased heat production in mammary gland development and lactogenesis triggers heat stress and is accompanied by the production of a large number of free radicals in order to maintain energy equilibrium. [29] A previously published study showed that SIF increased antioxidant capacity among postmenopausal females.…”
Section: Discussionmentioning
confidence: 99%
“…However, PTT cannot effectively relieve oxidative stress induced by ROS, which destroys cell proteins, membrane lipids, and nucleic acids, eventually leading to cell death and delayed wound healing . ROS-scavenging drugs exhibit enhanced therapeutic effects by relieving oxidative stress for wound healing; such drugs include nonsteroidal anti-inflammatory drugs, metabolic modulators, , natural antioxidants, and artificial nanozymes . Natural antioxidants with high activity and low toxicity have been used to eliminate endogenous ROS .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the research and development of antioxidants has become an important research topic worldwide. However, synthetic chemical antioxidants have some potential health hazards; therefore, the antioxidants prepared by the modification of natural products have attracted much attention [10][11][12].…”
Section: Introductionmentioning
confidence: 99%